2016
DOI: 10.18632/oncotarget.11334
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of RNAs in human lumbar disc degeneration

Abstract: Accumulating evidence indicates noncoding RNAs (ncRNAs) fine-tune gene expression with mysterious machinery. We conducted a combination of mRNA, miRNA, circRNA, LncRNA microarray analyses on 10 adults' lumbar discs. Moreover, we performed additional global exploration on RNA interacting machinery in terms of in silico computational pipeline. Here we show the landscape of RNAs in human lumbar discs. In general, the RNA-abundant landscape comprises 14,635 mRNAs (37.93%), 2,059 miRNAs (5.34%), 18,995 LncRNAs (49.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 51 publications
2
87
0
Order By: Relevance
“…LncRNAs have been shown to be differentially expressed in human degenerative NP tissue, and involved in the pathological processes of IDD, including inflammatory responses, apoptosis, proteoglycans degradation and ECM degeneration 3,8,15 . Therefore, the investigation of precise regulatory mechanism of lncRNA at the initial stage of IDD may be conductive to develop new diagnostic and therapeutic strategies for IDD and to improve the quality of life in IDD patients.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been shown to be differentially expressed in human degenerative NP tissue, and involved in the pathological processes of IDD, including inflammatory responses, apoptosis, proteoglycans degradation and ECM degeneration 3,8,15 . Therefore, the investigation of precise regulatory mechanism of lncRNA at the initial stage of IDD may be conductive to develop new diagnostic and therapeutic strategies for IDD and to improve the quality of life in IDD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the crucial role of Wnt signaling pathway in NPC senescence, nutrient deficiency, and ECM degradation, we attempted to screen for non‐coding RNAs that might be related to IDD pathogenic process and might be capable of regulating Wnt signaling. Data from GEO (GSE56081) indicate that H19 expression was significantly up‐regulated in human lumbar disc degeneration tissue samples . Moreover, H19 was found to be upregulated during osteogenesis in hMSCs; H19 significantly accelerated in vivo and in vitro osteoblast differentiation by serving as a ceRNA for miR‐141 and miR‐22 to de‐repress their shared target, β‐catenin, thus activating Wnt/β‐catenin signaling .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21] Mounting evidence has suggested that many lncRNAs are beregulated in diverse diseases such as tumours, diabetes, coronary heart disease, osteoarthritis and also IDD. [22][23][24][25][26][27][28][29] For example, Lan and colleagues 30 profiled lncRNA expression in degenerate disc tissues and normal adults' lumbar discs by microarray and found a total of 3081 differentially expressed lncRNAs. Wang et al 31 showed that knockdown of RP11-296A18.3 suppressed human NP cell proliferation and decreased the expression of collagen I and matrix metalloproteinase (MMP)-13.…”
mentioning
confidence: 99%